La cultura de planificación estratégica en hoteles y restaurantes de Machala. - Espinoza Rueda, Ricardo Alexander (My University, 2020)
The present research addresses one of the most important issues within the business field relating to culture to develop strategic planning in commercial organizations that allows them a more rigorous and effective control of their resources, this practice allows you to evaluate the management of personnel who are at the head of operations at the end of an economic period or at the end of a defined schedule, its application allowed to know its weaknesses that merit a type of solution and on the other hand its successes in order to strengthen them; In another context, it was also possible to know their existing threats and opportunities, a fundamental basis for establishing the pertinent strategies by their administrators and achieving the economic horizon desired by their investors; The chosen sector responds to the need for knowledge about the reality of these companies that are very common in the environment and that contribute to the advancement and progress of their environment through the generation of jobs, revitalization of the economy, circulation of money and taxes for the state; in its relevant part there is classified literature on strategy, strategic planning, decision making among others, which supports the conduct of the survey, as a technique for the collection of first-hand information, which once tabulated and analyzed allows to provide appropriate conclusions about the work done and that allows to know a little more about this important sector of the local economy.
La presente investigación aborda uno de los temas más importante dentro del ámbito empresarial relacionándose con la cultura para desarrollar la planeación estratégica en las organizaciones mercantiles que les permita un control más rigurosos y eficaz de sus recursos, esta práctica permite evaluar la gestión del personal que está al frente de las operaciones al finalizar un periodo económico o a su vez al finalizar una programación definida, su aplicación permitió conocer sus debilidades que ameriten un tipo de solución y por otra parte sus aciertos con el fin de fortalecerlos; en otro contexto, también se pudo conocer sus amenazas y oportunidades existentes, base fundamental para que se establezcan las estrategias pertinentes por parte de sus administrativos y se logre alcanzar el horizonte económico deseado por sus inversionistas; el sector escogido responde a la necesidad de conocimiento sobre la realidad de estas empresas que son muy comunes en el medio y que contribuyen al adelanto y progreso de su entorno a través de la generación de empleos, dinamización de la economía, circulación del dinero y tributos para el estado; en su parte pertinente se cuenta con literatura clasificada sobre estrategia, planeación estratégica, toma de decisiones entre otros, que sustenta la realización de la encuesta, como técnica para la recolección de información de primera mano, que una vez tabulada y analizada permite brindar las debidas conclusiones sobre el trabajo efectuado y que permite conocer un poco más de este importante sector de la economía local.
Keywords: CULTURA; PLANEACIÓN ESTRATÉGICA; RECURSOS; PERSONAL; DEBILIDADES